Yao & Artusio's anesthesiology problem-oriented patient management - Yao, Fun-Sun F., 1942-; Lippincott Williams & Wilkins (Philadelphia : Wolters Kluwer, 2021)
"A core text for anesthesia residents, Yao & Artusio's Anesthesiology is case-based and often used in preparation for oral boards. Sections are organized by system and all chapters follow the same format. After a brief presentation of a case, questions are posed regarding; medical disease and differential diagnosis, preoperative planning and preparation, intraoperative management, and postoperative management. Each question is then fully answered and discussed. The four classes of questions conform to the four areas of questioning at the oral boards so working through these considerations repetitively reinforces logical, critical thinking about patient management"--
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Anesthesia; Examination Questions; Anesthesia -- Examinations, questions, etc